2019
DOI: 10.1021/acs.energyfuels.9b00969
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Role of Alkyl Chain Length of the Inhibitors on Its Intercalation Inhibiting Mechanism in Sodium Montmorillonite

Abstract: Shale hydration and swelling are the major problems in using water-based drilling fluids in developing shale gas. In this work, the intercalation inhibiting mechanism of alkyl chain length on the swelling of sodium montmorillonite (Na-MMT) has been innovatively investigated using isothermal adsorption, adsorption kinetics, scanning electron microscopy, X-ray diffraction, cation exchange capacity, elemental analysis, and X-ray photoelectron spectroscopy techniques. The results indicate that an increase in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Since the backbone of HMDA and BPEI is hydrophobic, the backbone of HMDA and BPEI can squeeze the water molecules out, thus synergistically enhancing the inhibitory performance. The experimental results also confirm that a suitable hydrophobic chain length can enhance the inhibitory performance . The two adsorption groups of inhibitors, lying flat, adsorbed on the Mt (001) surface.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…Since the backbone of HMDA and BPEI is hydrophobic, the backbone of HMDA and BPEI can squeeze the water molecules out, thus synergistically enhancing the inhibitory performance. The experimental results also confirm that a suitable hydrophobic chain length can enhance the inhibitory performance . The two adsorption groups of inhibitors, lying flat, adsorbed on the Mt (001) surface.…”
Section: Resultssupporting
confidence: 55%
“…The experimental results also confirm that a suitable hydrophobic chain length can enhance the inhibitory performance. 22 The two adsorption groups of inhibitors, lying flat, adsorbed on the Mt (001) surface. These results are consistent with the arrangement of inhibitor in the interlamellar space of Mt, as determined from the results obtained using XRD analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the increase of population of interlayer metal sites and the electron conductivity and mobility of Na + ions, the charge/mass transport have been significantly improved. It is demonstrated that the organic molecules can be successfully inserted into the interlayer of 2D-layered materials to engineer the ionic channels, giving rise to a favorable electrochemical performance. In light of these research works, we propose to introduce n -alkylamine into layers via an acid–base mechanism to manipulate interlayer distances, which promote the ion and electron transfer in electrode materials and helps to maintain the layered structure . The experimental results reveal that the n -propylamine (PA)-intercalated NCO (pNCO) had enhanced ability to adsorb Na + ions, prevent structural deformation, and hinder the degradation of performance.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that shale formations are prone to be hydrated during shale gas drilling processes, leading to downhole complexities such as borehole collapse, tight hole, stuck pipe, etc. [1,2]. Thus, the stability of wellbore is of great importance for shale gas exploitation [3].…”
Section: Introductionmentioning
confidence: 99%